Exploring the use of Virtual Surgical Planning (VSP) in Maxillofacial Reconstructions - Yadavalli Guruprasad; Shyamalendu Laskar; Mohammed Mohsin Moosabhai Patadiya; Inderjit Murugendrappa Gowdar; Anuj Singh Parihar; Karandeep Singh; Ramanpal Singh Makkad (Wolters Kluwer Medknow Publications, 2024)
Background: Virtual surgical planning (VSG), also known as computer-assisted reconstruction, has started to become the norm for more complex patients in many centers in recent times. Aim: This study was conducted to evaluate the VSG in maxillofacial reconstruction surgery. Methods and Materials: This study included 20 patients who underwent surgery for maxillofacial reconstruction. The study participants were divided into two main categories: Category 1: Conventional surgical planning (CSG). Category 2: VSG. The surgical planning in both categories, including the evaluation of volume of defect, length, width, and height of graft, to be placed. Results: The gap between defect to be reconstructed and graft placed was greater in CSG as compared to VSG. The distance of graft from actual location was lesser in VSG as compared to CSG. The findings were significant statistically. Frequency of success was 93.21% and 97.47%, respectively. The frequency of success was greater in VSG as compared to CSG. Conclusion: Virtual surgical planning is more effective in maxillofacial reconstruction surgery.